Effects of Elbow Crutch Locomotion on Gluteus Medius Activation During Stair Ascending - De la Fuente, Carlos; Neira, Alejandro; Torres, Gustavo; Silvestre, Rony; Roby, Matias; Yañez, Roberto; Herrera, Sofia; Martabit, Virgina; McKay, Isabel; Carpes, Felipe P. (Frontiers in Bioengineering and Biotechnology, 2022)
The use of elbow crutches may alter muscle activation during locomotion, but there is a lack of knowledge how the nervous system adapts the hip muscle activation during an the stair ascending. Hence, we determined the acute effects of elbow crutches locomotion on Gluteus Medius (GM) activity during stair ascending. Ten healthy men (22.0 ± 0.47 years) were enrolled in a comparative analytic cross-sectional study. Different stair ascending using elbow crutches (one or two crutches, ipsi, or contralateral use, and load or unload limb conditions) was used. The outcomes and measures were EMG signals recorded from anterior, middle, and posterior portions of GM were compared between the conditions. Multiple comparisons were performed (α = 5%). The lateral use of crutches increased the activation for ipsilateral use, the number of crutches increased the activation with two crutches and three points, and the load/unload of the extremity increased the activation in the loaded limb. The contralateral use and unload limb revealed lower GM activation. Elbow crutches alters the GM activation during ascending stairs; the more important factors were the lateral use of crutches, the number of crutches and the load/unload of extremity. Stairs ascent using two-crutches with three points in the unloaded limb elicits lower activation, while the higher activation was observed for the loaded extremity. This knowledge is useful for the activation management of frontal pelvis-hip muscles stabilizers for better planning on who uses or will use crutches.